Energy Efficient RF Remote Control for Dimming the Household Applainces - Rajesh Singh; Piyush Kuchhal; Anita Gehlot; Sushaban Choudhary (Institute of Advanced Engineering and Science, 2015)
During recent years there is a strong trend towards radio frequency (RF) remote controls as it is delivering even more comfort to the users and increased usability with high robustness of the RF links. Lower power consumption with new features and security make RF remote control systems more competitive with widely used IR remote control systems. In this paper we propose, a RF module based real time system, which is an integrated system designed to control the dimming or speed of the appliances. Zigbee module is used as RF module to establish wireless link between Remote and appliance section having 9600kbs baud rate and range of 100m. Dimming control circuits is part of appliances section which is used to control the appliances corresponding to signals generated by the remote section. This system provides energy efficient solution for household uses. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.7046